Capacity Relational and Networking Start-Ups in the Ecosystem Entrepreneurship : A Review Qualitative Based on Conceptual Study - Novrizal, Novrizal; Nurhasanah, Sri Utami (LPPM STIE Kasih Bangsa, 2024)
This qualitative literature review explores the role of relational capacity and networking in the success of start-ups within entrepreneurial ecosystems. The study synthesizes findings from existing research to highlight how strong relational capacity facilitates access to essential resources, information, and market opportunities. It also underscores the importance of diverse and extensive networks in fostering innovation and adaptability. The dynamic nature of entrepreneurial ecosystems, supported by favorable policies and a culture of innovation, is crucial for start-up growth. Despite challenges in building effective networks, digital technology presents new opportunities for start-ups to expand their networks and leverage virtual resources. This study concludes that effective relational capacity and networking are critical for the sustainability and success of start-ups. Limitations include the scope of literature and the need for empirical validation through further research.